Avaliação agronômica e valor nutricional do sorgo forrageiro BRS 658 com diferentes arranjos populacionais - Porfirio, Magno Daniel (2019)
The aim of this study was to evaluate the productive potential and nutritional quality of sorghum BRS 658 with different population arrangements. The experimental design in randomized complete blocks, in a double factorial scheme (3x3) with four blocks, in which there were factors such as spacing (3) being 0.5 m; 1.0 m and 1.5 m and population densities (3) being 50; 100 and 150 thousand plants ha-1. Statistical analysis was performed using the SAS statistical program. There were no interactions for the sources of population variation and row space to any of the variables analyzed. For the best results are 86440 and 86491 kg MV ha-1 at 1 meter spacing and population density of 50,000 plants ha-1, respectively. For the largest dry matter, the spacing of 1 m with the value of 11157 kg ha -1 independent density, for the population density the highest evaluation was 22946 kg ha -1 for 50 thousand plants. For stem diameter and height there was difference only for the studied densities, with 28.69 mm and 303.82 cm for the densities of 150 and 50 thousand plants ha-1, respectively. For variable dry matter, mineral matter and organic matter there was linear effect of density independent of spacing, with higher results of 264.50 g kg-1 MN, 70.34 and 938.90 g kg-1 MS for the densities of 50, 150 and 50 thousand plants ha-1, respectively. The variable PIDN presented quadratic effect for density independent of spacing with higher result of 510.20 g kg-1 PB for density of 50 thousand plants ha-1. The overall average for total digestible nutrients was 567.3 g kg-1 MS, for in vitro dry matter digestibility 425.9 g kg1 MS, for in vitro neutral detergent fiber digestibility 551.5 g kg-1 MS for in vitro digestibility of organic matter 570.7 g kg-1 MS, for soluble carbohydrates 78.31 g kg-1 MS and for total carbohydrates was 846.7 g kg-1 MS. For the carbohydrate fractionation the average observed for fraction A + B1 was 160.6 g kg-1 TC, for fraction B2 472.9 g kg-1 TC and fraction C 366.5 g kg-1 TC. The different population arrangements evaluated do not alter the yield, agronomic and bromatological characteristics, nutrient digestibility, carbohydrate concentration and total digestible nutrients of BRS 658 forage sorghum. Row space 1.0 m and sowing density 50 one thousand plants ha-1 results in higher yield of green and dry matter, sown in the density of 150 thousand plants ha-1 presents smaller height with larger stem and mineral matter diameter.